Pengaruh Penggunaan Bahan Ajar Leaflet Terhadap Hasil Belajar Peserta Didik di UPTD SMPN 4 Gunungsitoli Selatan - Harefa, Gita Claresta Evelyn; Gulo, Hardikupatu; Waruwu, Toroziduhu; Zega, Novelina Andriani (BEST Journal (Biology Education, Sains and Technology), 2024)
This research is motivated by the results of initial observations conducted by researchers at UPTD SMP Negeri 4 Gunungsitoli where it was found that students' critical thinking skills towards learning materials were still low due to the learning process which only refers to printed books and rarely uses interesting teaching materials. The purpose of this study was to determine the effect of the use of leaflet teaching materials on the science learning outcomes of grade IX students at UPTD SMP Negeri 4 Gunungsitoli Selatan. This study is a pre-experimental study with a one-group pretest-posttest design and uses a quantitative research approach. The population in this study included all grade IX students at UPTD SMP Negeri 4 Gunungsitoli Selatan, and the research sample was taken from 31 grade IX-A students. The instrument used in this study was a student learning outcome test. Based on the results of the study, it shows that the use of leaflet teaching materials at UPTD SMP Negeri 4 Gunungsitoli Selatan has been proven to have a significant influence in improving student learning outcomes. This teaching material has the potential to be maintained and further developed to support a better learning process.